2021
DOI: 10.1007/s10639-021-10461-y
|View full text |Cite
|
Sign up to set email alerts
|

Question paper generation through progressive model and difficulty calculation on the Promexa Mobile Application

Abstract: Mobile learning has been increased in past years and has attracted the interests of academicians and educators in the past many years especially in higher education. The mobile-based online test is the buzzing in the current pandemic time. Institutions need to use online learning as a powerful tool for conducting exams and assess the students effectively. Integrating technology in education can be advantageous for universities and help engage better results for students. Therefore, it is important to understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Nonetheless, the above analysis revealed that Remote Proctoring platforms raise ethical concerns over-and-above those affecting live and in-person exam invigilation. These concerns include an uncertain risk of academic unfairness associated with AI-informed judgement (Singh et al, 2021 ), further diminution of student privacy and autonomy, and increased distrust towards institutions that are bastions of social values. Another fear, partially dependent on these former fears, is that these platforms could contribute to the issues of growing surveillance, liberty and privacy loss, mining of massed personal data, and dubious instances of AI decision-making.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Nonetheless, the above analysis revealed that Remote Proctoring platforms raise ethical concerns over-and-above those affecting live and in-person exam invigilation. These concerns include an uncertain risk of academic unfairness associated with AI-informed judgement (Singh et al, 2021 ), further diminution of student privacy and autonomy, and increased distrust towards institutions that are bastions of social values. Another fear, partially dependent on these former fears, is that these platforms could contribute to the issues of growing surveillance, liberty and privacy loss, mining of massed personal data, and dubious instances of AI decision-making.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The categorization of the DL of the questions makes it easier to interpret, for example, easy, medium, and difficult questions. A lot of literature refers to this interpretation by making other criteria (Singh et al, 2021) and (Turkmen & Caner, 2020). The DL is classified as follows.…”
Section: Discussionmentioning
confidence: 99%
“…The first introduced a mobile educational application providing theoretical knowledge and question-based tests for computer engineering undergraduate students (Kayaalp & Dinc, 2022). Singh et al (2021) devel-oped a progressive model calibrating the difficulty level based on learner understanding in Computer Science education, which will prepare institutions for the transition from paper-based to mobile-based online tests. Voshaar et al (2022) measured how a gamified mobile learning application influenced exam success on a course in the field of Business and Administration Studies.…”
Section: Assessment and Evaluationmentioning
confidence: 99%